PRINCIPLES OF WATER HAMMER INTERFEROMETER - Bergant, Anton (Journal of Energy Technology, 2024)
This paper presents a novel water hammer interferometer. In essence, it is an acoustic tube interferometer using the controlled closure of two valves. The device generates two water hammer wavesthat interfere with each other along the liquid-filled pipeline. The superposition of the two waves can generate pressure head variations of different frequencies and amplitudes. The frequency and shape of pressure histories are controlled via the delayed closure of one of the two valves. The interference phenomena in an ideal pipeline system are described with the aid of basic water hammer theory.